2015
DOI: 10.17567/dfd.46691
|View full text |Cite
|
Sign up to set email alerts
|

The Shaping Ability of Five Different Nickel-Titanium Rotary Instruments in Simulated Root Canals

Abstract: The aim of this study was to compare the shaping ability of a recently introduced instrument (Revo-S) in comparison with the four current instruments (HeroShaper, Mtwo, ProTaper, RaCe) in simulated root canals. Material and methods: Nickel-Titanium systems (n=15 resin in each case) were used to prepare 34-35° curved and S-shaped simulated root canals in clear resin blocks. The width of resin removal was measured by comparing the pre-and postoperative images under a stereomicroscope. The amount and direction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(42 reference statements)
2
1
0
1
Order By: Relevance
“…While there was a high statistically significant difference among the groups at D1, D2, D3, D5, D6 , D7 and D8 these points represent the apical and coronal curvature and probably these differences could be noticed because , at these points of the curvature there is a higher stress on the instrument owing to the critical changes on the relationship of diameter and flexibility this agreed with the study of Farah and Al-Gharrawi (30) , in which they found a statistically significant difference among the Protaper , Biorace and SAF groups at level 6 mm. ProTaper instruments showed the greatest material removal on the inner sides of the apical curvatures and outer side of coronal curvatures, resulting in a marked straightening of the canals, which is in accordance with a recent study of Göktürk et al (25) , who restudied the shaping ability of five different systems in S-shaped canals in resin blocks and showed that the ProTaper instruments have a tendency to straighten both curved parts of the canal this may be due to the ProTaper Universal finishing files have a greater taper at the apical part of the instrument (F1, .07 and F2, .08), leading to increased stiffness or rigidity, similar findings obtained by…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While there was a high statistically significant difference among the groups at D1, D2, D3, D5, D6 , D7 and D8 these points represent the apical and coronal curvature and probably these differences could be noticed because , at these points of the curvature there is a higher stress on the instrument owing to the critical changes on the relationship of diameter and flexibility this agreed with the study of Farah and Al-Gharrawi (30) , in which they found a statistically significant difference among the Protaper , Biorace and SAF groups at level 6 mm. ProTaper instruments showed the greatest material removal on the inner sides of the apical curvatures and outer side of coronal curvatures, resulting in a marked straightening of the canals, which is in accordance with a recent study of Göktürk et al (25) , who restudied the shaping ability of five different systems in S-shaped canals in resin blocks and showed that the ProTaper instruments have a tendency to straighten both curved parts of the canal this may be due to the ProTaper Universal finishing files have a greater taper at the apical part of the instrument (F1, .07 and F2, .08), leading to increased stiffness or rigidity, similar findings obtained by…”
Section: Discussionsupporting
confidence: 91%
“…This may be due to use more successive files in ProTaper system. Similar finding was found in the research of Göktürk et al (25) , who studied the shaping ability of greater HeroShaper, Revo-S, ProTaper Universal, Mtwo, and RaCe. The HeroShaper and Revo-S showed lower centering ability than the other groups in simulated curved canals in the apical area.…”
Section: Discussionsupporting
confidence: 90%
“…Yüksek esnekliği ve kesme verimliliği nedeniyle nikel-titanyum (Ni-Ti) döner aletler kök kanallarını şekillendirmek için yaygın olarak kullanılmaktadır. [1][2][3][4] Döner aletlerin klinik kullanımdaki pratikliği tercih sebebi olsa da, iki farklı mekanizmaya (torsiyonel ve döngüsel yorgunluk) bağlı olarak Ni-Ti eğelerde oluşan alet kırılması tedaviyi olumsuz etkilemektedir. [5][6][7] Torsiyonel yorgunluk, eğenin ucu kanal içerisinde sıkıştığı zaman sap kısmının dönme hareketinin devam etmesi sonucunda meydana gelmektedir.…”
Section: Gġrġġunclassified
“…The previous comparative studies involving Mtwo and Protaper instruments showed that no instrument separated during the instrumentation. 16,42 Another recent study which used individual torque limit and rotational speed programmed in the file library of the Endo IT motor for each RaCe, K3 and Mtwo file noted that six RaCe files, four K3 instruments and no Mtwo instruments fractured; however a total of 8 Mtwo instruments permanently deformed. 11 Yared et al 43 reported that instrument locking, deformation and separation did not occur with any of the three torque values (20,30, and 55 Ncm).…”
Section: 27-29mentioning
confidence: 99%